Linear to quadratic crossover of Cooper-pair dispersion relation - Adhikari, S. K.; Casas, M.; Puente, A.; Rigo, A.; Fortes, M.; Solis, M. A.; de Llano, M.; Valladares, A. A.; Rojo, O. (Elsevier B.V., 2001)
Cooper pairing is studied in three dimensions to determine its binding energy for all coupling using a general separable interfermion interaction. Also considered are Cooper pairs (CPs) with nonzero center-of-mass momentum (CMM). A coupling-independent linear term in the CMM dominates the pair excitation energy in weak coupling and/or high fermion density, while the more familiar quadratic term prevails only in the extreme low-density (i.e., vacuum) limit for any nonzero coupling. The linear-to-quadratic crossover of the CP dispersion relation is analyzed numerically, and is expected to play a central role in a model of superconductivity (and superfluidity) simultaneously accommodating a Bardeen-Cooper-Schrieffer condensate as well as a Bose-Einstein condensate of CP bosons. (C) 2001 Elsevier B.V. B,V. All rights reserved.
Keywords: Cooper pairs; Bose-Einstein condensation; exotic superconductivity; superfluidity